Remediation of Petroleum Contaminated Soils: Biological, Physical, and Chemical Processes - Riser-Roberts, Eve (CRC Press, 2009)
This book combines the results of current research with essential background material to provide complete, in-depth coverage of every aspect of in situ and ex situ bioremediation, as well as an extensive overview of the physical and chemical processes currently available for treating petroleum-contaminated soils. Critical information has been collected and assembled under one cover to provide a convenient reference for anyone who must contend with this worldwide problem.